6x+5=4x+48

Simple and best practice solution for 6x+5=4x+48 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+5=4x+48 equation:



6x+5=4x+48
We move all terms to the left:
6x+5-(4x+48)=0
We get rid of parentheses
6x-4x-48+5=0
We add all the numbers together, and all the variables
2x-43=0
We move all terms containing x to the left, all other terms to the right
2x=43
x=43/2
x=21+1/2

See similar equations:

| (4x+1)=3x+17 | | 6(X+1)+3(X-3)=4x•5 | | 2x+x+4/7=7 | | 10x=- | | 4-7x=10x-2x-26 | | 4v-72=v | | 7x+2(-4x-18)=-24 | | -2=-8+3g | | 22.8+-9.6x=61.2 | | 12x+5=4-x | | 9x+18-8x=-3-13 | | 8y-53=y+24 | | -5w/8=15 | | (3x-7)(x-1)=-1 | | 2x+3x=10-10x | | 4–z=-2z | | 16x=5-(-11 | | 8.75c+12.50=56.25 | | 6s=s+10 | | -42=6/5y | | M/8+m/2=3/4 | | 5x-3(-x-15)=-135 | | 7(-6x-5)=161 | | -3(2n-5)=7n-24 | | (4x-25)=(2x-1) | | 6a–25=a | | 2x^2-5x-10=2 | | -28=-4/7v | | -16-6x=-6(x=3) | | -16-6x=-6(x=3 | | -3(8+3x)=48 | | 6t=t+40 |

Equations solver categories